Governance of global value chains in response to food safety and certification standards: the case of shrimp from Vietnam - NhuongTran; Bailey, Conner; Wilson, Norbert L.W.; Phillips, Michael (Elsevier, 2013)
We use global value chain (GVC) theory to understand governance of Vietnam’s shrimp farming industry. We describe this GVC as buyer-driven with important food safety standards imposed by governments of importing countries and new certification systems promoted by nongovernmental organizations (NGOs). Governance relations are clear between governments in importing countries and Vietnam, and between importers and NGOs. Governance relations become more fragmented further down the chain where large numbers of small-scale producers and traders operate. This fragmentation may adversely affect access to the most lucrative markets and have the unanticipated effect of marginalizing small-scale farmers and traders.